1987
DOI: 10.1007/bf00249789
|View full text |Cite
|
Sign up to set email alerts
|

Response properties of the parabrachio-thalamic taste and mechanoreceptive neurons in rats

Abstract: A total of 66 taste and 33 mechanoreceptive neurons were isolated from the parabrachial nucleus (PB) of rats. Among them, 39 taste and 8 mechanoreceptive neurons were identified as parabrachio-thalamic relay (P-T) neurons on the basis of antidromic activation from either or both sides of the thalamic taste areas (TTAs). On average, the P-T taste neurons produced larger response magnitudes than the non-P-T taste neurons, and whereas about half the P-T taste neurons were NaCl-best, only a small number of the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 18 publications
5
46
3
Order By: Relevance
“…tralateral VPMpc, respectively. These results confirmed earlier tract tracing studies and the reports of Ogawa and colleagues (51,52) that taste neurons in the PbN project to the VPMpc bilaterally. We found that a much higher proportion of tasteresponsive PbN neurons project to either or both of the ipsilateral or contralateral VPMpc (95.6%) than were reported by Ogawa and colleagues (55-59%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…tralateral VPMpc, respectively. These results confirmed earlier tract tracing studies and the reports of Ogawa and colleagues (51,52) that taste neurons in the PbN project to the VPMpc bilaterally. We found that a much higher proportion of tasteresponsive PbN neurons project to either or both of the ipsilateral or contralateral VPMpc (95.6%) than were reported by Ogawa and colleagues (55-59%).…”
Section: Discussionsupporting
confidence: 92%
“…Norgren (47) demonstrated that a subset of NaCl and/or thermal-responsive PbN neurons in the rat were antidromically driven by stimulation of the ipsilateral amygdala and/or VPMpc. Ogawa and colleagues (51,52) reported in two separate studies that 55-59% of taste neurons in the PbN project to either or both of the ipsilateral or contralateral VPMpc in the rat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The core of the PB''G'' corresponds precisely to the region in which most of the gustatory neurons were recorded (Norgren, 1974;Norgren and Pfaffman, 1975;Ogawa et al, 1987;Halsell and Travers, 1997), confirming that the PB''G''-VPpc pathway described in the present study conveys primarily gustatory messages. In addition, our study points out that the more medial portion of the pPBm, the properties of which were not clearly determined, also project to the VPpc.…”
Section: Functional Implications Of Pb Projectionssupporting
confidence: 80%
“…Ventral to the bc, the pPB area centered in the waist area (pPBwa) and the medial subnucleus (pPBm) deal mainly with gustatory functions Leonard, 1971, 1973;Norgren and Pfaffmann, 1975;Norgren, 1978Norgren, , 1995Ogawa et al, 1987;Halsell and Travers, 1997).…”
mentioning
confidence: 99%